Design and simulation of an integrated circuit for the control of a PAP motor, using VHDL programming - Utrilla Salazar, Darío (2006)
This report describes the design of an integrated circuit developed to control stepper motors (PAP), using an FPGA device, obtained through VHDL programming and advanced digital design techniques. First, the basic characteristics of stepper motors are presented, then the procedures carried out, starting with the description of the control environment used. Next, the design of the integrated circuit for the control of the stepper motor and its implementation in an FPGA through advanced digital design tools are detailed. Finally, the simulations obtained from the design showing its operation are shown.